2009
DOI: 10.1016/j.evolhumbehav.2009.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of eye movements when male and female observers judge female attractiveness, body fat and waist-to-hip ratio

Abstract: Behavioural studies of the perceptual cues for female physical attractiveness have suggested two potentially important features; body fat distribution (the waist-to-hip ratio or WHR) and overall body fat (often estimated by the body mass index or BMI). However none of these studies tell us directly which regions of the stimulus images inform observers' judgments. Therefore, we recorded the eye-movements of 3 groups of 10 male observers and 3 groups of 10 female observers, when they rated a set of 46 photograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
73
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 58 publications
13
73
3
Order By: Relevance
“…4). This is consistent with previous literature that the waist-hip is an important determinant of attractiveness (Singh, 1993) and women attend to the mid and lower torso when assessing attractiveness (Cornelissen et al, 2009). However, Cornelissen et al (2009) also found women gazed frequently at the chest, another region important for attractiveness (Singh & Young, 1995), whereas we found no differences between viewing time at the upperbody and leg regions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…4). This is consistent with previous literature that the waist-hip is an important determinant of attractiveness (Singh, 1993) and women attend to the mid and lower torso when assessing attractiveness (Cornelissen et al, 2009). However, Cornelissen et al (2009) also found women gazed frequently at the chest, another region important for attractiveness (Singh & Young, 1995), whereas we found no differences between viewing time at the upperbody and leg regions.…”
Section: Discussionsupporting
confidence: 93%
“…This discrepancy might be caused by the clothing. The body's chest area was modestly covered in our study (even in the tight clothing condition), but was nude in Cornelissen et al (2009) which might draw more attention to this area.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…We chose to focus our analysis on these two regions as previous research has demonstrated they are the most crucial for eliciting differences in sexual preference in heterosexual men. Specifically, men gaze sooner and longer at these regions when viewing adult female stimuli (Cornelissen et al, 2009;Dixson, Grimshaw, Linklater, & Dixson, 2011;Hewig et al, 2008). However, when viewing images of males there is no difference in gaze allocation to these regions (Hall et al, 2011(Hall et al, , 2012.…”
Section: Discussionmentioning
confidence: 88%
“…In support of this, previous research has demonstrated that differences in waist-hip ratios and breast sizes influence attractiveness judgments (Connolly, Slaughter, & Mealey, 2004;Furnham, Swami, & Shah, 2006;Furnham, Tan, & McManus, 1997), which can also be evidenced by differences in gaze towards these regions. For example, Suschinksy, Eilas and Krupp (2007) found that men judged figures of a lower waist-to-hip ratio as more attractive, and also dedicated more gaze to the upper-body and waist-hip regions of these figures when compared to figures with higher waistto-hip ratios, and Cornelissen, Hancock, Kiviniemi, George and Tovee (2009) showed that men and women tend to gaze at the stomach and chest region when making attractiveness judgments.…”
Section: Introductionmentioning
confidence: 99%